Association between amoxicillin administration and outcomes in critically ill patients with acute kidney injury - Luo, Xinyao; Zhou, Weijian; Wan, Dingyuan; Peng, Jing; Liao, Ruoxi; Su, Baihai (Frontiers in Pharmacology, 2024)
This study assessed the effect of amoxicillin on outcomes in intensive care unit (ICU) patients with acute kidney injury (AKI), focusing on mortality rates and acute kidney disease (AKD) occurrence.We conducted a retrospective cohort analysis utilizing data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The study included ICU patients diagnosed with AKI to assess the effects of post-admission amoxicillin administration on 30-day and 90-day mortality rates and AKD incidence.We employed Cox proportional hazards models, propensity score matching, and inverse probability of treatment weighting to control for potential confounders.Results: Among 24,650 AKI patients, 676 (2.7%) received amoxicillin. The results indicated significantly lower mortality rates at 30 days (hazard ratio [HR] 0.54, 95% confidence interval [CI] 0.42-0.69) and 90 days (HR 0.64, 95% CI 0.52-0.77) in the amoxicillin group compared to non-recipients. Additionally, amoxicillin administration was associated with a reduced incidence of AKD (HR 0.49, 95% CI 0.36-0.65) but resulted in a modestly increased length of hospital stay (mean difference [MD] 1.95 days, 95% CI 1.15-2.75). A dose-response relationship was evident, with higher doses (>875 mg) further decreasing mortality rates. Subgroup analysis revealed consistent benefits across most patient groups.Conclusions: Amoxicillin administration following ICU admission in patients with AKI was associated with improved survival rates and a lower incidence of AKD, highlighting its potential as a therapeutic measure for AKI management.